The coming of post-industrial society : - Bell, Daniel (Basic Books, 1973)
Contents: From Industrial to Post-Industrial Society: Theories of Social Development; From Goods to services: The Changing Shape of the Economy; The Dimensions of Knowledge and Technology: The New Class Structure of Post-Industrial Society